Impact of Grazing Regimes, Landscape Aspect, and Elevation on Plant Life Form Types in Managed Arid Montane Rangelands - Msadek, Jamila; Tlili, Abderrazak; Moumni, Marwa; Louhaichi, Mounir; Tarhouni, Mohamed (Elsevier, 2022)
Arid steppes, with scattered vegetation, are commonly qualified as degraded ecosystems. Their natural vegetation cover is affected by both abiotic stresses and human activities and, therefore, suitable managements are needed for their sustainability. This study was carried out in the mountain rangeland chain of Matmata (southern dryland of Tunisia) during the springs of 2 rainy yr, 2019 and 2020. Our aims were to evaluate the impact of three grazing regimes (grazing exclusion [over 42 ys; 1978−2020]; seasonal [protected in spring and summer and grazed in autumn and winter, since the 1960s]; and continuous grazing [control; grazed over time]) on the cover of some plant life forms (Raunkiaer, Noy-Meir, and Grime types), under various conditions (sites, aspects, and elevations). To achieve this goal, the pseudoreplicated-nested design was applied, taking into account the site locations (grazing regimes), aspects (exposure to sunlight), and elevations. The cover of the retained plant life forms was measured using the quadrat point method. The main results showed that plant life forms are strongly affected by the grazing regime since the chamephytes (Ch_R), arido-active (AA_NM), and competitive stress-tolerant species (CS_G) are higher under seasonal grazing than control. All these species are qualified as less resistant to grazing. However, arido-passive (AP_NM), ruderal stress-tolerant (RS_G), and therophytes (Th_R) seem to be more resistant to grazing. Studying the impact of grazing management on the plant life form types provides useful information to find the most adapted species for rangeland sustainability all around the world.